2023
DOI: 10.1098/rspb.2023.0988
|View full text |Cite
|
Sign up to set email alerts
|

Confusion will be my epitaph: genome-scale discordance stifles phylogenetic resolution of Holothuroidea

Abstract: Sea cucumbers (Holothuroidea) are a diverse clade of echinoderms found from intertidal waters to the bottom of the deepest oceanic trenches. Their reduced skeletons and limited number of phylogenetically informative traits have long obfuscated morphological classifications. Sanger-sequenced molecular datasets have also failed to constrain the position of major lineages. Noteworthy, topological uncertainty has hindered a resolution for Neoholothuriida, a highly diverse clade of Permo-Triassic age. We perform th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…This is in fact the expected behavior if topological incongruence is driven by biological factors such as ILS (Mendes & Hahn 2016). While some have argued that deep recalcitrant nodes are linked to ancient events of ILS (e.g., Cai et al 2021;Hime et al 2021;Mongiardino Koch et al 2023;Song et al 2023), it has also been suggested that topological incongruence at deep timescales is more likely to be caused by methodological issues related to loss of signal and model inadequacy (Gatesy & Springer 2014;Richards et al 2018). While our analyses were not designed to test this phenomenon, our results are contrary to those expected if ILS was the main driver of topological conflict at ancient nodes.…”
Section: Discussionmentioning
confidence: 75%
“…This is in fact the expected behavior if topological incongruence is driven by biological factors such as ILS (Mendes & Hahn 2016). While some have argued that deep recalcitrant nodes are linked to ancient events of ILS (e.g., Cai et al 2021;Hime et al 2021;Mongiardino Koch et al 2023;Song et al 2023), it has also been suggested that topological incongruence at deep timescales is more likely to be caused by methodological issues related to loss of signal and model inadequacy (Gatesy & Springer 2014;Richards et al 2018). While our analyses were not designed to test this phenomenon, our results are contrary to those expected if ILS was the main driver of topological conflict at ancient nodes.…”
Section: Discussionmentioning
confidence: 75%